Rapid alcoholysis of Jatropha curcas oil for biodiesel production using ultrasound irradiation - Irwan, M. (Diponegoro University, 2017)
The biodiesel synthesis through alcoholysis process of triglyceride from Jatropha curcas using different type of alcohol, such as: methanol, ethanol, isopropyl alcohol and tert-butanol, was conducted in the presence of potassium hydroxide (KOH) as a catalyst under 35 kHz frequency ultrasound irradiation. The optimum conditions, such as: alcohol to jatropha oil molar ratio, concentration of catalyst, reaction temperature, and reaction time, were found to be 7:1 of alcohol to jatropha oil molar ratio, 0.5 % of KOH, temperature of reaction at 35 °C, within the reaction times of 15 minutes. The results obtained for the different types of alcohol were 62.77 %, 57.93 %, 51.64 %, and 46.77 % for methanol, ethanol, isopropyl alcohol, and tert-butanol, respectively.